Cancers of the Head & Neck - Burtness, Barbara
Cancers of the Head & Neck is an open access, peer-reviewed journal dedicated to publishing articles on pre-clinical and translational research, as well as research related to the clinical management of head & neck cancers. This includes cancers of the oral cavity, pharynx, larynx, paranasal sinuses, nasal cavity and salivary glands. Articles related to the aetiology, pathophysiology, prevention, diagnosis, treatment and survivorship of these cancers are all considered.  Topical areas of interest include, but are not limited to: • Biologic insights and novel targets • HPV associated cancers of the head and neck, including epidemiological studies • Biomarker studies – including applications and limitations of currently established biomarkers, reports on new and emerging biomarkers and the shift from prognostic to predictive use biomarkers to personalise treatment • In vitro and in silico modelling • Clinical trials of novel agents or paradigm • Advances in immunotherapy and integrating immunotherapeutic approaches into care • Novel aspects of surgical management including use of minimally invasive surgical techniques in conjunction with chemoradiotherapy • Patient related outcomes, including survivorship issues, follow-up care, rehabilitation and speech therapy As an open access, online journal, Cancers of the Head & Neck provides a high visibility platform for the publication of original research and expert reviews. The journal serves as essential reading for medical oncologists, radiation oncologists, surgical oncologists, speech therapists, rehabilitation medicine providers, as well as basic and translational researchers, drug developers, dental practitioner and other allied healthcare professionals.